2013
DOI: 10.1111/j.1476-5381.2012.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

The case for induced pluripotent stem cell‐derived cardiomyocytes in pharmacological screening

Abstract: The current drug screening models are deficient, particularly in detecting cardiac side effects. Human stem cell-derived cardiomyocytes could aid both early cardiotoxicity detection and novel drug discovery. Work over the last decade has generated human embryonic stem cells as potentially accurate sources of human cardiomyocytes, but ethical constraints and poor efficacy in establishing cell lines limit their use. Induced pluripotent stem cells do not require the use of human embryos and have the added advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 127 publications
(173 reference statements)
2
59
0
Order By: Relevance
“…Cardiomyocytes differentiated from iPSCs show concentration-dependent responses to cardioactive drugs, including beating frequency and contractility, which are consistent with clinical effects. 17 Additionally, these cells express S1P 1 and S1P 3 receptors (results not shown). Compound 1-P showed a concentration-dependent decrease in cardiomyocyte beating rate, with a no-effect concentration of 0.1 nM.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 86%
“…Cardiomyocytes differentiated from iPSCs show concentration-dependent responses to cardioactive drugs, including beating frequency and contractility, which are consistent with clinical effects. 17 Additionally, these cells express S1P 1 and S1P 3 receptors (results not shown). Compound 1-P showed a concentration-dependent decrease in cardiomyocyte beating rate, with a no-effect concentration of 0.1 nM.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 86%
“…To overcome these shortcomings, human-induced pluripotent stem cell-derived cardiomyocytes are now often used for cardiotoxicological screenings. 22 However, thus far, human-induced pluripotent stem cell-derived cardiomyocytes cannot produce dense monolayers of phenotypically homogeneous ventricular cardiomyocytes for high-resolution optical mapping. 23 We hence used NRVM monolayers to study the effects of LUF7244 on the proarrhythmic potential of 3 inadvertent K v 11.1 blockers by optical voltage mapping.…”
Section: Nrvm Monolayers As Model For Studying Druginduced Long Qt Symentioning
confidence: 99%
“…These cause differences in each species' tolerance to chemical agents (Price et al, 2008), and might yield false-positive or -negative results when human toxicity is evaluated using experimental animals and cells. Tests using many kinds of known cardioactive compounds have shown that hiPS-CMs are useful for evaluation of pharmacological responsiveness in humans (Sirenko et al, 2013;Khan et al, 2013). Thus, assay systems using hiPS-CMs are likely to provide accurate and efficient screening of candidate drugs.…”
Section: Discussionmentioning
confidence: 99%
“…CMs derived from hiPS cells (hiPS-CMs) are artificially generated source of human tissue, and their potential for use in medical and pharmacological applications has been intensively examined (Funakoshi et al, 2016;Kawamura et al, 2012;Khan et al, 2013;Sirenko et al, 2013). In the pharmacological field, hiPS-CMs have been confirmed to show appropriate responsiveness to known cardioactive compounds (Sirenko et al, 2013), and hiPS-CMs are expected to contribute to efficient screening of candidate drugs (Khan et al, 2013). HiPS-CMs are becoming a powerful tool to evaluate human responses.…”
Section: Introductionmentioning
confidence: 99%